Effects of trans-Cinnamic Acid on Expression of the Bean Phenylalanine Ammonia-Lyase Gene Family - Mavandad, Mehrdad (1990)
Using DNA probes specific for the three members of the bean (Phaseolus vulgaris L.) phenylalanine ammonia-lyase (PAL) gene family, we have studied the effects of the product of the PAL reaction, trans-cinnamic acid (CA), on the appearance of individual PAL transcripts in suspension cultured bean cells. Concentrations of CA in excess of 10(−4) molar inhibited appearance of elicitor-induced transcripts encoding PAL1, PAL2, and PAL3 when added to the cells at the same time as fungal elicitor. Addition of CA 4 hours postelicitation caused a major reduction in the levels of all three PAL transcripts, but with different kinetics and subsequent rates of recovery. The inhibition of accumulation of PAL1, PAL2, or PAL3 transcripts, measured 3 hours after exposure to elicitor, as a function of the time of addition of CA postelicitation reflected the different rates of appearance of the three PAL transcripts in the presence of elicitor alone. The inhibitory effects of CA as seen on PAL transcripts were not observed for the constitutively expressed transcript H1, or the elicitor-inducible 1,3-β-D-glucanase. Analysis of in vitro translated polypeptides showed that some elicitor-induced mRNA activities were not down-regulated by CA, and that a number of other mRNA activities were induced by CA, thus providing further evidence for specificity in the action of CA on bean cells. Treatment of elicited cells with L-α-aminooxy-β-phenylpropionic acid, a potent and specific inhibitor of PAL activity, resulted in maintenance of elevated PAL transcript levels beyond 12 hours postelicitation, this effect being greatest for PAL transcripts 2 and 3. Our results are consistent with a model in which CA, or a derivative, could act as a component in a regulatory feedback system operating at the level of phenylpropanoid gene transcription.